Synergy of inelastic and elastic energy loss: Temperature effects and electronic stopping power dependence. (1st January 2016) - Zarkadoula, Eva; Xue, Haizhou; Zhang, Yanwen; Weber, William J.
Abstract: A combination of an inelastic thermal spike model suitable for insulators and molecular dynamics simulations is used to study the effects of temperature and electronic energy loss on ion track formation, size and morphology in SrTiO3 systems with pre-existing disorder. We find temperature dependence of the ion track size. We also find a threshold in the electronic energy loss for a given pre-existing defect concentration, which indicates a threshold in the synergy between the inelastic and elastic energy loss.